Automobile electrical and electronic systems : automotive technology : vehicle maintenance and repair - Denton, Tom. (New York : Routledge, 2012)
"As electrical and electronic systems become increasingly more complex and fundamental to the workings of modern vehicles, understanding these systems is essential for automotive technicians. For students new to the subject, this book will help to develop this knowledge, but will also assist experienced mechanics in keeping up with recent technological advances. This new edition includes information on developments in hybrid car technology, GPS, multiplexing, and electronic stability/vehicle dynamics control. In full colour and covering the latest course specifications, this is the guide that no student enrolled on an automotive maintenance and repair course should be without.This textbook will help you learn all the skills you need to pass Level 3 vehicle electrical and electronic systems courses or related modules from City and Guilds, IMI and BTEC, and is also ideal for higher level ASE, AUR and other qualifications"--
"This textbook will help you learn all the skills you need to pass Level 3 vehicle electrical and electronic systems courses or related modules from City and Guilds, IMI and BTEC, and is also ideal for higher level ASE, AUR and other qualifications. As electrical and electronic systems become increasingly more complex and fundamental to the workings of modern vehicles, understanding these systems is essential for automotive technicians. For students new to the subject, this book will help to develop this knowledge, but will also assist experienced mechanics in keeping up with recent technological advances. This new edition includes information on developments in hybrid car technology, GPS, multiplexing, and electronic stability/vehicle dynamics control. In full colour and covering the latest course specifications, this is the guide that no student enrolled on an automotive maintenance and repair course should be without"--
First ed. published: 1995. Second ed. published: 2000. Third ed. published: 2004.
Includes index.
Keywords: Automobiles -- Electric equipment; Automobiles -- Electronic equipment; TECHNOLOGY & ENGINEERING / Automotive; TRANSPORTATION / Automotive / Repair & Maintenance